THE HERO JOURNEY OF ALICE IN “ALICE’S ADVENTURE IN WONDERLAND” BY LEWIS CARROL; ARCHETYPAL APPROACH - Nurdiana, Nurdiana; Evyanto, Winda (LPPM Universitas Putera Batam, 2019)
This research was carried out to figure out the hero’s journey stages of the character Alice in novel Alice’s Adventure in Wonderland by doing the archetypal study. The aims of this research are indicate the separation stage and return stage. Moreover, this research is a descriptive qualitative research and the data is collected through library research. The result will presented using informal method. As the result of this research, it is found that not all stages in separation and return stage that proposed by Joseph Campbell can be found in Alice’s Adventure in Wonderland. There are only three stages out of five separation stages and one stage out of six return stages that can be found in the novel. However, the novel can still be categorized as a hero’s journey story. Even though the hero’s journey stage is not complete, the story still reached it finish line and the reader can understand the story well.